Angiopoietin-Like Proteins 2 and 3 in Children and Adolescents with Obesity and Their Relationship with Hypertension and Metabolic Syndrome - Zahra Arab Sadeghabadi; Mitra Nourbakhsh; Mohammad Alaee; Mona Nourbakhsh; Seyedeh Sara Ghorbanhosseini; Roya Sharifi; Maryam Razzaghy-Azar (International Journal of Hypertension)
Background. Angiopoietin-like protein 2 (ANGPTL2) is one of the adipocyte-derived inflammatory factors which connects obesity to insulin resistance. ANGPTL3 has a direct role in regulation of lipid metabolism. The objective of this study was to evaluate ANGPTL2 and ANGPTL3 in childhood obesity and their relationship with metabolic syndrome. Methods. 70 children and adolescents, 35 obese and 35 normal-weight subjects, were enrolled in this research after complete clinical examination and anthropometric evaluations. Serum ANGPTL2 and ANGPTL3 and insulin were measured by enzyme-linked immunosorbent assay (ELISA). Homeostatic model assessment of insulin resistance (HOMA-IR) was calculated and used to estimate insulin resistance (IR). Colorimetric methods were used for the assessment of fasting plasma glucose (FPG), LDL-C, HDL-C, total cholesterol (TC), and triglyceride (TG). Results. The levels of ANGPTL2 and ANGPTL3 were significantly higher in obese subjects than those in controls, but they did not differ significantly in subjects with or without IR. ANGPTL3 was found to be significantly elevated in obese children with metabolic syndrome (MetS) in comparison with those without MetS. Both of the studied ANGPTLs were positively correlated with BMI, systolic blood pressure (SBP), diastolic blood pressure (DBP), TC, and LDL-C. The correlation between ANGPTL3 and either TC or LDL-C remained significant after adjusting for BMI. Conclusion. Serum ANGPTL2 and ANGPTL3 were elevated in obesity and associated with blood pressure and indices of metabolic syndrome, suggesting that they might be involved in the advancement of obesity-related hypertension and metabolic syndrome.